Orchestrating Public Opinion How Music Persuades in Television Political Ads for US Presidential Campaigns, 1952-2016 - Christiansen, Paul (Amsterdam University Press, 2017)
Orchestrating Public Opinion for the first time examines in detail music's persuasive role in political ads for US presidential campaigns. Studies on political ads tend to consider music something of an afterthought, innocuous accompaniment for a narrator. In this book Christiansen takes an opposing view, arguing that music is crucial to an ad's construction. In some cases, it is even determinative: that is, all other elements-images, voiceover, sound effects, written text, and so on-can be circumscribed by and interpreted in relation to music. This book presents for the first time correspondence between campaign officials and ad agencies, storyboards, and music scores related to ads such as Eisenhower's "I Like Ike" or Reagan's "Morning in America."Engaging music seriously through detailed musical analysis as well as exploring music's relation to visual and textual elements in ads, Orchestrating brings together disparate approaches toward understanding the surreptitious rhetoric of music.